ANEMIC PROFILE IN DIABETES -A REVIEW - Dr Sridevi-G (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Diabetes mellitus (DM) commonly called ―Diabetes‖ is a metabolic disease characterized by hyperglycemia and related symptoms. The clinical picture of Diabetes is presented with polyurea, polydipsia, polyphagia, weight loss and extreme fatigue.